Colecistite aguda decorrente de hemorragia intraluminar da vesícula biliar após trauma abdominal fechado - Salomão,Renato Manganelli (2008)
Isolated gallbladder injury following abdominal blunt trauma is rare and early diagnosis is difficult to make, particularly when no other organ is injured. However, ultrasonography is valuable for investigating gallbladder injuries. We report a case of isolated gallbladder blunt trauma presented as acute cholecystitis with hemobilia. In isolated blunt traumatic injury to the gallbladder, treatment options vary depending on the specific injury. The characteristics of blunt trauma injuries to the gallbladder and their appropriate management are discussed.